PEMANFAATAN MEDIA BERBASIS INFORMASI TEKNOLOGI (IT) DALAM PEMBELAJARAN FIQIH - Rahman, Abdul; Zalnur, Muhammad; Rahmat, Rahmat (Yayasan Rahmat Islamiyah, 2024)
With the advancement of technology, teachers must have the understanding and ability to use technology as a learning tool. This research aims to examine the extent to which the use of Information Technology (IT)-based media in Fiqh Learning at the Guguak Randah Integrated Private Madrasah Aliyah (MA-ST) can be understood by students. This research is field research where the location of this research is at the Guguak Randah Private Integrated Madrasah Aliyah (MA-ST). In this research the author uses a qualitative descriptive method with primary data sources, namely 1 Fiqh teacher and secondary data of the principal and students as well as in The data collection efforts required in this research, the author used several data collection techniques and tools through interviews, observation and documentation. The results of this research can be concluded that the use of Information Technology (IT)-based media in Fiqh Learning is quite effective and easy for students to understand where teachers use PowerPoint media in face-to-face learning and WhatsApp groups to support learning even though there are obstacles such as limited focus and limited time. in making power point media and teaching materials, but this does not discourage fiqh teachers in using Information Technology (IT) based media.